(untitled) (Cardiovascular Journal, 2016)
Background: Objective of the study was to determine the outcome of school student led smoke free home program. Methods: A study was conducted among the school student of Bangladesh, during the period of July to November 2010.Students were used as an agent to create an environment in the house discussing with their parents and other members of the family to reduce indoor smoking and as well as help smokers in quitting smoking. Result: During the five months intervention indoor smoking prevalence reduced by 61.6% but smoking prevalence among fathers reduced only 3.2%. Conclusion: This small intervention of short duration indicates that motivation through school student have a high potential of making home smoke-free. Cardiovasc. j. 2016; 8(2): 135-137